The rapid course of small cell lung cancer and treatment options - case report - Łomża, Aleksandra; Rodzajewska, Anna; Kowaleczko, Magda; Łaba, Łukasz; Chmielewska, Izabela; Milanowski, Janusz (Journal of Education, Health and Sport, 2022)
Small cell lung cancer (SCLC) is a disease with an unfavorable prognosis. Factors contributing to losing prognosis include: systemic disease, many comorbidities, smoking and the patient’s low performance status (PS). Early diagnosis and treatment initiation seem to be the most significant in the diagnostic and therapeutic process. However, most of patients are diagnosed in metastatic stage. The basic method of metastatic SCLC treatment is chemotherapy, which, according to the latest research (CASPIAN, IMPower133), can be linked to immunotherapy, which is associated with a major improvement in therapeutic efficiency. We present a case of 64-year-old man with a rapidly progressive course of small cell lung cancer, where the fulminant course of the disease led to death within about one month of the first imaging examinations, equally preventing the initiation of systemic treatment. The presented case shows how important is paying attention to the first symptoms, timely diagnosis of the disease and initiation of effective and targeted therapy in patients with SCLC.